Формування педагогічних компетентностей у студентів спеціальності «Професійна освіта. Економіка. Економічна та бізнес-освіта» засобами інноваційних технологій (на прикладі дисципліни «Методика професійного навчання») - Ковригін, Богдан Євгенович (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
Мета дослідження – теоретично обґрунтувати, розробити та експериментально перевірити методику формування педагогічних компетентностей у студентів спеціальності «Професійна освіта. Економіка. Економічна та бізнес-освіта» засобами інноваційних технологій (на прикладі дисципліни «Методика професійного навчання».

The purpose of the study is to theoretically substantiate, develop and experimentally verify the methodology for the formation of pedagogical competencies in students of the specialty "Vocational education. Economics. Economic and business education" by means of innovative technologies (on the example of the discipline "Methodology of vocational training".
Formation of pedagogical competencies in students of the specialty "Vocational education. Economics. Economic and business education" by means of innovative technologies (on the example of the discipline "Methodology of vocational training"
Keywords: SOCIAL SCIENCES::Social sciences::Pedgogical work; педагогічні компетентності; студенти спеціальності «Професійна освіта. Економіка. Економічна та бізнес-освіта»; педагогічна підготовка; інноваційні технології; pedagogical competencies; students of the specialty "Professional Education. Economics. Economic and Business Education"; pedagogical training; innovative technologies